Compliance rates with local and national business taxes: Evidence from Kampala, Uganda - Rose Camille Vincent; Stephan Dietrich; Kyle McNabb (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper investigates business tax compliance in a multilevel tax structure with limited coordination. We study the case of Kampala, where firms are taxed at national and local levels-by the Uganda Revenue Authority and the Kampala Capital City Authority, respectively-and where the agencies operate quasi-independently. We begin by merging large-scale administrative tax data from the separate registries of the two agencies. In doing so, we have a rare opportunity to understand firm compliance with their due payments to the URA and KCCA. Following the idea of a reciprocal exchange of taxation for public services, we also examine whether neighbouring infrastructure and the immediate environment of the firms are associated with patterns and spatiality of business tax noncompliance. Our results suggest that non-compliance with local business taxation is widespread, even for large firms that are fully incorporated and paying corporate income tax to the URA. Less than 20 per cent of corporate income tax filers are found to be paying trade licences to the KCCA for their businesses or for all their branches on an annual basis. The results of the merging exercise also convey crucial concerns about the inability of tax administrations to properly identify and monitor taxable businesses. The parallel registries create loopholes and pose significant challenges to revenue mobilization efforts across the board, as only a small percentage of firms comply with their due payments to tax institutions on a yearly basis. Non-compliance is found to be more prevalent in villages with poor public infrastructure, showing clear signs of spatial correlation.
Keywords: H70; H71; H72; O10; 330; business taxation; tax institutions; tax compliance; Uganda